Comparative effectiveness of playing golf to Nordic walking and walking on acute physiological effects on cardiometabolic markers in healthy older adults: a randomised cross-over study. Issue 1 (6th February 2023) - Kettinen, Julia; Tikkanen, Heikki; Venojärvi, Mika
Abstract : Objectives: The acute effects of aerobic exercise on cardiometabolic markers are well documented in younger healthy individuals, but the same effects in older adults have not been elucidated. As such, this study compares the acute effects of three different types of age-appropriate aerobic exercises on cardiometabolic markers. Methods: Healthy older golfers (n=25, 16 male and 9 female, 68±4 years) were enrolled in a randomised cross-over experiment. We compared the effects of three different acute aerobic exercises (18-hole golf, 6 km Nordic walk, 6 km walk) on blood pressure, blood glucose and blood lipid profile in a real-life environment. Results: In the between-group comparison, playing golf resulted in a difference in blood glucose (golf: 0.01±1.0 mmol/L, walk: 1.3±0.9 mmol/L, p<0.001) compared with walking and triglycerides (golf: 0.13±0.2 mmol/L, Nordic walk: 0.31±0.2 mmol/L, walk: 0.23±0.2 mmol, p=0.012) and high-density lipoprotein cholesterol (golf: 0.04±0.06 mmol/L, Nordic walk: −0.02±0.06 mmol/L, walk: −0.02±0.07 mmol/L, p=0.002) compared with Nordic walking and walking. In addition, all groups had significant decreases (p<0.001) in systolic blood pressure, and Nordic walking and walking also demonstrated a decrease in diastolic blood pressure (p<0.05). Conclusion: Acute bouts of aerobic exercise improved cardiovascular profile in healthy older adults. Despite the lower exercise intensity of golf, the longer duration and higher energy expenditure appeared to have a more positive effect on lipid profile and glucose metabolism compared with Nordic walking and walking. Trial registration number: ISRCTN10007294 .